2020
DOI: 10.1371/journal.pone.0240377
|View full text |Cite
|
Sign up to set email alerts
|

Volar locking plate versus external fixation for unstable dorsally displaced distal radius fractures–A 3-year cost-utility analysis

Abstract: To investigate the cost-effectiveness of Volar Locking Plate (VLP) compared to External Fixation (EF) for unstable dorsally displaced distal radius fractures in a 3-year perspective. Methods During 2009-2013, patients aged 50-74 years with an unstable dorsally displaced distal radius fracture were randomised to VLP or EF. Primary outcome was the incremental costeffectiveness ratio (ICER) for VLP compared with EF. Data regarding health effects (Quality-adjusted life years, QALYs) was prospectively collected dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…In a randomized study of patients aged 65 years and older with displaced DRFs, Hassellund et al 24 found that volar plating was not cost effective compared with nonsurgical treatment from the health care perspective despite significantly higher health-related quality of life associated with surgical treatment. In a randomized study of patients aged 50–74 years with unstable dorsally displaced fractures, Saving et al 25 found that volar plating resulted in higher costs and a smaller quality of life benefit compared with external fixation. Yoon et al 26 concluded that casting and percutaneous pinning were the most cost-effective treatment strategies for closed extra-articular fractures and closed unstable fractures, respectively, in patients aged 60 years and older.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized study of patients aged 65 years and older with displaced DRFs, Hassellund et al 24 found that volar plating was not cost effective compared with nonsurgical treatment from the health care perspective despite significantly higher health-related quality of life associated with surgical treatment. In a randomized study of patients aged 50–74 years with unstable dorsally displaced fractures, Saving et al 25 found that volar plating resulted in higher costs and a smaller quality of life benefit compared with external fixation. Yoon et al 26 concluded that casting and percutaneous pinning were the most cost-effective treatment strategies for closed extra-articular fractures and closed unstable fractures, respectively, in patients aged 60 years and older.…”
Section: Discussionmentioning
confidence: 99%
“…All transition-state probabilities and ranges can be seen in Table 1 . 3 , 5 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , …”
Section: Methodsunclassified
“…Postoperative casting also uses expensive resources, such as time spent in the OR and visits to outpatient clinics for cast fixing or removal. 18 Moreover, the restoration of wrist function and the reduction of impairment is important considering that more than 50% of DRF patients are still of working age. A mean sick leave duration of 4–12 weeks has been reported, which means sick leave after DRF has an important socioeconomical role.…”
Section: Introductionmentioning
confidence: 99%
“…After primary intervention, DRFs are associated with the use of multiple resources, including operative interventions, outpatient visits and rehabilitation. Postoperative casting also uses expensive resources, such as time spent in the OR and visits to outpatient clinics for cast fixing or removal 18. Moreover, the restoration of wrist function and the reduction of impairment is important considering that more than 50% of DRF patients are still of working age.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the variability and complexity of a single series of fractures or the distinct techniques utilized between the cases, the clear conclusions are difficult to be obtained. [ 17 19 ]…”
Section: Introductionmentioning
confidence: 99%